Psychological Capital as A Moderating Influence of Budget Participation and Transformational Leadership Style on Managerial Performance of Star Hotels - Ni Putu Ayunda Prihantini; I Ketut Yadnyana; I Ketut Sujana; Ni Made Adi Erawati (Journal Research of Social Science, Economics, and Management, 2024)
This research aims to examine and analyze the role of psychological capital (PsyCap) as a moderator in the influence of budget participation and transformational leadership style on managerial performance in star hotels. This research uses a quantitative approach with a population of 18 hotels from 3 to 5 stars in Buleleng Regency. The sampling technique used was a saturated sample, with 134 respondents. Data was collected through questionnaires (google form) and directly (print out). Data analysis was carried out using structural equation modeling (SEM) with SmartPLS 3.2.9 software. The research results show that budget participation and transformational leadership style have a positive effect on managerial performance. Psychological capital has also been proven to strengthen the influence of budget participation and transformational leadership style on managerial performance. It is hoped that the results of this research can help hotels to improve managerial performance through increasing cooperation between leaders and employees, higher budget participation, implementing a transformational leadership style, and positive improvements in the psychological aspects of employees so that they have psychological capital that supports achieving company goals. The study provides several recommendations for future researchers to include macroeconomic factors such as GDP (Gross Domestic Product) growth, inflation, interest rates, and unemployment rates in their research. This inclusion can provide important external context.